2002
DOI: 10.2139/ssrn.334420
|View full text |Cite
|
Sign up to set email alerts
|

Diversification in Banking: Is Noninterest Income the Answer?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

61
549
9
33

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(652 citation statements)
references
References 14 publications
61
549
9
33
Order By: Relevance
“…Moreover, De-Young and Roland (2001) argue that the substitution of traditional operations with fee-income activities is related to an instability of earnings, while Acharya et al (2006) show that banks with higher inclusion of non-interest income activities in their portfolio perform less efficiently than banks with lower involvement in fee-income operations. In the same manner, Stiroh (2004) and Lepetit et al (2008) find a positive association between fee-based revenue and bank risk. Yet for saving banks an increase in fee-income could have a positive impact on performance (Chiorazzo et al, 2008), as these banks engage in both interest and non-interest income operations and thereby diversify their risk (De-Young and Rice, 2004).…”
Section: H1: Lower Default Risk Asserts a Positive Impact On Performamentioning
confidence: 64%
“…Moreover, De-Young and Roland (2001) argue that the substitution of traditional operations with fee-income activities is related to an instability of earnings, while Acharya et al (2006) show that banks with higher inclusion of non-interest income activities in their portfolio perform less efficiently than banks with lower involvement in fee-income operations. In the same manner, Stiroh (2004) and Lepetit et al (2008) find a positive association between fee-based revenue and bank risk. Yet for saving banks an increase in fee-income could have a positive impact on performance (Chiorazzo et al, 2008), as these banks engage in both interest and non-interest income operations and thereby diversify their risk (De-Young and Rice, 2004).…”
Section: H1: Lower Default Risk Asserts a Positive Impact On Performamentioning
confidence: 64%
“…Similarly, Stiroh (2004) documents that noninterest diversification is negatively linked with performance. Acharya et al (2006) provide results suggesting that there are diseconomies of scope that arise through weakened monitoring incentives and a poorer-quality loan portfolio when a risky bank expands into additional industries and sectors, complementing the agency-theoretic analysis of the boundaries of a bank's activities as proposed in Cerasi and Daltung (2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, in contrast to the lending business, fee-based activities require less regulatory capital, which suggests a higher degree of financial leverage and therefore leads to a higher earnings volatility. Indeed, DeYoung and Roland (2001) and Stiroh (2004a) find empirical evidence that reliance on non-interest activities increases the volatility of large U.S. banks. In general, only a few papers identify empirical evidence that combined lending and non-interest activities cause diversification benefits and therefore lead to risk reduction.…”
Section: Review Of Literaturementioning
confidence: 99%
“…By contrast, there are some studies (mainly for the US banking market) that have shown a positive and significant influence of diversification through non-interest income on earnings volatility. 5 Stiroh (2004a) analyzes the potential benefit of income diversification for U.S. banks. Since the growth of net interest and net non-interest income in the period 1984-2001 is increasingly correlated, he concludes that the diversification benefits decreased during the period in question.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation